Nauka sztuki kupieckiej w Krakowie XVI–XIX wieku. Zarys problemu - Gadocha, Marcin (Biuletyn Historii Wychowania, 2012)
The article is a survey and an attempt to bring closer the questions connected with the education of future tradesmen in Cracow from the 16th century until the first half of the 19th century. Thus far, there has been no thorough study devoted to this topic. In the 16th century, young adepts of trade would start learning this occupation in their father’s business, further family’s business or in the dynamically developing trading houses in Cracow. In the 16th c. and 17th c. there was no merchants’ guild in Cracow, which could oversee the process of learning the “art of trade”. Only the establishment of the Merchants’ Congregation in 1722 brought about changes in this respect. Ultimately, in the new statute of the Congregation from 1833, the new principles of training were formulated. Candidates had to present their birth certificate, the recommending certificate written by their parents or foster parents. Moreover, the candidate had to be able to read, write and calculate in Polish or German. Learning took three years in the 16th and 17th centuries; in the 18th century this period was prolonged, in the 19th century lasted from 4 to 6 years. According to the author, the problem still requires further in-depth research. After the archival query, it seems that there are good possibilities to obtain valuable material connected with mercantile art in Cracow.